A linguist's view: Khoe-Kwadi speakers as the earliest food-producers of southern Africa - Güldemann, T. (Southern African Humanities, 2021)
I propose that the spread of pastoralism into southern Africa is associated with a Pre-Bantu population that was originally characterized by the following profile: it spoke a language of the Khoe-Kwadi family which was structurally closer to Kwadi than to Proto-Khoe; had a stone-age food-producing culture with a focus on pastoralism; and did not have a typical southern African Khoisan genetic profile. This hypothesis implies that not all groups lumped together in the spurious category of 'southern African Khoisan' emerged within southern Africa and were 'pristine' hunter-gatherers. Several indications regarding the possible origin of this population in East Africa are also discussed. To cite this article: Güldemann, T. 2008. A linguist's view: Khoe-Kwadi speakers as the earliest food-producers of southern Africa. Southern African Humanities 20: 93-132.